Glycemic Variability: An Independent Predictor of Mortality and the Impact of Age in Pediatric Intensive Care Unit - Du, Yuhui; Liu, Chengjun; Li, Jing; Dang, Hongxing; Zhou, Fang; Sun, Yuelin; Xu, Feng (Frontiers in Pediatrics, 2020)
Objective: To compare the ability of different indices of glycemic variability (GV) to predict prognosis in critically ill children, and investigate whether heterogeneity of glucose control may exist within this population. Methods and Results: The retrospective study of GV record the patients admitted to the pediatric intensive care unit(PICU), Children’s Hospital of Chongqing Medical University from January 2016 to December 2016. Mean glucose level (MGL) and four indices of GV are calculated: standard deviation (SD); coefficient of variation (CV); mean amplitude of glycemic excursion (MAGE) and glycemic lability index (GLI). The primary endpoint is 28-day mortality. Survivors and non-survivors exhibit significant differences with respect to SD, CV, MAGE, and GLI (p<0.05 for all); GLI is superior to other indices and also show an independent association with ICU mortality (odds ratio [OR], 1.082; 95% confidence interval [CI], 1.031–1.135; P < 0.01). On sub-group analysis disaggregated by quartiles of MGL and GV, younger subjects (age ≤36 months) experience significantly higher mortality in the lowest quartile of mean glucose and highest quartile of GV; the older children (age >36 months) experience significantly higher mortality in the highest quartiles of mean glucose and GV. Conclusion: GV is closely associated with mortality and GLI is the strongest predictor of outcomes among all glucose parameters. Our study is the first report showing that age is a potentially important modifier of the association between GV, MGL, and mortality among critically ill children.